(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
In recent years, there has been a notable uptick in the exploration of underwater optical wireless communications (UOWC) as a viable alternative for efficient high-speed data transmission beneath the sea. This technology employs optical wavelengths in dedicated point-to-point connections, sharing similarities with free space optical (FSO) communications and laser satellite links. By harnessing specific wavelengths, UOWC achieves impressive data transfer rates, as demonstrated in recent research showcasing broadband communications over substantial distances. This technology holds promise in various applications such as environmental protection, seawater exploration, military operations, and emergency alarms. However, the underwater environment poses challenges due to scattering and severe absorption, making the channel a complex medium to navigate. Additionally, accurate localization presents a significant challenge, leading to improperly adjusted connections that adversely affect signal propagation quality. This work provides an overview emphasizing the significance of optical wireless communications underwater and its role in contemporary applications. It delves into the crucial factors influencing optical signals and explores the types of connections and configurations used in transmitting and receiving channels..